Faktor-Faktor Yang Memengaruhi Kinerja UMK Pempek Di Kota Palembang (Jurnal Agribisnis Indonesia, 2025)
Micro and Small Enterprises (MSEs) are vital to the national economy due to their role in labor absorption and poverty alleviation, with the pempek industry in Palembang City serving as a prominent sector that faces challenges such as limited capital, low innovation, and traditional management. This study aims to identify the characteristics of these SMEs and analyze the influence of internal and external factors on their business performance within the specific context of Palembang City. Using a mixed-methods approach, data were collected from 200 purposively selected SME actors through surveys and interviews, then analyzed using Structural Equation Modeling (SEM-PLS) to examine variables including human resources, finance, marketing, government policy, and socio-economic support. The findings reveal that both internal and external factors significantly impact performance; specifically, stronger internal capabilities in HR and finance lead to better growth, while external factors provide essential support both directly and indirectly. Although the sector in Palembang City is dominated by educated, productive-aged women with high development potential, weaknesses in financial access and technological utilization persist. The SEM-PLS model successfully explains the variations in business dynamics, demonstrating that a synergy between internal management and institutional support is crucial for the sustainability of pempek businesses. This research provides a comprehensive framework for stakeholders to strengthen the local culinary industry by addressing specific operational and capital needs in Palembang City.